Perancangan E-Commerce Berbasis Opencart untuk Meningkatkan Pemasaran dan Penjualan Produk Kerajinan Di Pasar Bawah Bukittinggi - Rizki Dongoran, Roni; Annas, Firdaus; mu'tada, Muhammad (Yayasan Lembaga Studi Makwa, 2024)
Pasar Bawah Bukittinggi is a traditional trading center that sells a variety of local handicraft products, but businesses in this market still face limited access to online marketing and sales in the midst of digital era competition. This research aims to design and implement OpenCart-based e-commerce using the PPE (Planning, Development and Evaluation) method to improve marketing and sales of craft products. System needs analysis was conducted through interviews and observations of business actors. The e-commerce development included product management features, online transactions, and social media integration. Evaluation involved end-user testing and analysis of sales data before and after implementation. The results showed that OpenCart-based e-commerce improved market competitiveness, expanded consumer reach, and increased product sales by 35%. Businesses that previously had limited access to technology now have a platform that simplifies the transaction and marketing process. In addition, this research contributes to the digitalization efforts of MSMEs in Indonesia, particularly in helping traditional markets adopt technology to improve competitiveness. Globally, this model can be adapted by traditional markets in developing countries to encourage the digitalization of the traditional trade sector. Thus, the implementation of OpenCart-based e-commerce in Pasar Bawah Bukittinggi proves that the traditional market is not just a market.